Serviceology for Smart Service System Selected papers of the 3rd International Conference of Serviceology - Sawatani, Yuriko; Spohrer, James; Kwan, Stephen; Takenaka, Takeshi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
Services are key activities in a globalized economy and they also underlie the quality of life of local residents. The advanced work presented in this book was selected from the proceedings of the Third International Conference on Serviceology (ICServ2015), held July 7-9, 2015, in San Jose, CA, USA. The conference was supported by the Society for Serviceology. The society was established in 2012 in Japan to explore the scientific systematization of services and to promote technological developments for solutions to industrial issues. This book provides a useful general guide to the state of the art in the theory and practice of services. It can also serve as a valuable reference book for researchers in a wide range of fields from engineering to marketing and economics.
A new service class scheme for service innovation in Japanese automation industry -- Design of Service Ecosystem Based on Interactive Design Support in the case of Job-hunting Support Services -- A Method for Supporting Customer Model Construction Using a Topic Model for Public Service Design -- A Proposal of the Emotion Hierarchy Diagram for Designing the Service Processes -- A Creed for Service Designers -- Design Support System for Sightseeing Tours -- Service Data Model in Design Support System for Sightseeing Tours -- Design of Localized Science Education Program for Cultivating Inter-generational Community -- How to generate sustainable services? -- A Service Innovation for reducing Food Adulteration problem in Bangladesh -- Challenges to Deploy Service Design in Organizations: Analysis through "Scaling Up" Workshops -- Generalized Service Process Expressed by Context-Free Grammar -- Realization of Mobility as a Service in View of Ambient Intelligence -- Customer Experience in traditional and modern retail formats: Case study of Vietnam -- A combinatorial auction based approach to staff shift scheduling in restaurant business -- Enhancing Kitchen Layout and Training to Improve Management and Employee Satisfaction at a Multiproduct Japanese Cuisine Restaurant -- The efficient provision of culture-sensitive services - a modularization approach -- Nurse Bed Care Activity Analysis for Intelligent Training Service -- An Evolving Service System in Microfinance: A Case Study in BRAC, Bangladesh -- Developing an ad-hoc Questionnaire Model for extracting Consumer behaviour in Service Encounter -- Method of Building Conceptual Preference Model based on Personal Purchase Records for Retail Service improvement -- Are Superior Services Always Good for Satisfaction Formation? Consideration of Indebtedness to a Contact Person -- An analysis of key factors of the "Omotenashi-consumption" in restaurants -- Structural Equation Modeling of Purchase Funnel -- Toward Sports training service with the interactive learning platform -- VR/ServE: A Software Toolset for Service Engineering using Virtual Reality -- Productivity improvement and stress reduction by showing information to a surveillance worker -- Skill Evaluation and Education Services for Bed-Care Nursing with Sliding Sheet with Regression Analysis -- "Kizkey" is the key for a better care service -- Role of Servicing Activity Visualization in Quality Control Circle -- Physiological Detection of Satisfaction for Services by Body Motion Wave revealing Unconscious Responses reflecting Activities of Autonomic Nervous Systems -- The effects of wait time, length of stay and hospital rehabilitation on the structure of patient satisfaction -- Service Satisfaction and the Consciousness-Attitude Gap for Foreign Tourists Visiting Japan -- Service as Artifact: Reconsideration of Value Co-creation -- Development of Conceptual Framework for Value Co-creation of Service based on the Japanese Governmental Service Science Research Program -- An Interactive Model for the Synthesis of Service Functions through Use Processes -- Statistical Estimation of Software Quality in Hospital Information System -- A Consideration of the Pricing Structure of Aesthetic Services: An Example of Consumer Decision Making with Ambiguous Information -- Designing New Business Development Program Based on Systems Engineering Methodology with Participatory System Analysis in Small and Mid-Size Enterprise -- Qualitative Simulation for Early- Stage Service Design -- Impacts of Seasonal Factors on Travel Behavior -- Basic analysis of GPS trajectory data for Eight months -- -- Collaborative Innovation Centers (CICs): Toward Smart Service System Design -- The value of the word of mouth for tasting rice -- Dispersed Energy Storage and Its Effect on Market Efficiency in Electricity Trading with Distributed Power Resources: An Experimental Economics Study.
Keywords: Industrial Management; Production management; Engineering design; Computer networks .; Industrial Management; Operations Management; Engineering Design; Computer Communication Networks